Accounting and financial reporting guidelines for small and medium-sized enterprises (SMEGA) (UN New YorkUS, 2004)
Seeks to assist in the preparation of general-purpose financial statements for SMEs in developed and developing countries as well as in economies in transition.
Contents: Level 2 Guidance. - Level 3 Guidance